Potensi Ekonomi dan Kelayakan Budidaya Tanaman Lada (Piper nigrum) di Kecamatan Purehu Kabupaten Kolaka Utara - Syamsuri, Syamsuri; Alang, Hasria (Jurnal Ilmiah Membangun Desa dan Pertanian, 2021)
This study examined pepper cultivation's economic potential and feasibility in Purehu Village, Purehu District, North Kolaka Regency, Southeast Sulawesi. The research was conducted from January until February 2021. The research approach used by the author is qualitative with descriptive methods. Data collection in this study was carried out through in-depth interviews with informants, observation, and documentation. The informant or subject of this research is the head of a farmer's family in Purehu Village. The variable of this research was the economic potential and feasibility cultivation of pepper—analysis of data using income cost difference (R-C) and Revenue Cost Ratio (R/C). The results showed that pepper cultivation (P. nigrum) in Purehu Village, Purehu District, could generate an average profit of IDR84.000.000 for the first harvest, and pepper cultivation in that area is very worth continuing based on the R/C ratio. The study concludes that pepper cultivation in Purehu Village has very high economic potential (good) because the farmers' profits are quite large each year, and pepper cultivation in that place is very feasible to continue.